Representations of adult attachment and shame in parents of children on the autism spectrum - Conrad, Charlotte Engberg; Lauritsen, Marlene Briciet; Færk, Emil; Jakobsen, Helle; Thomsen, Per Hove; George, Carol (Frontiers in Psychology, 2025)
Social communication disabilities in children on the autism spectrum challenge parenting. This is the first study to examine mental representations of adult attachment and shame in parents of children on the autism spectrum. Thirty-seven parents of children diagnosed with autism spectrum disorder (mean age 5.17 years) from middle to high-income households participated in the study. The Adult Attachment Projective Picture System was used to evaluate adult attachment patterns and representations as well as shame outcomes. All but three parents were classified as having insecure adult attachments. Almost half of the participants (45.9%) were classified as having unresolved attachments. All parents showed representations of a shamed self. Deep shame associated with attachment trauma was more common than normative shame. The sample was divided into regulated (secure, dismissing, and preoccupied combined) versus unresolved individuals. There were no significant group differences regarding shame or shame outcomes. The discussion addresses how the high frequency of insecure attachment representations and shame may affect parenting. This prevalence suggests that clinicians support families with children on the autism spectrum and introduce the topic of shame.